Ketamine Versus Tramadol Effectiveness as Postoperative Oral Analgesics on Pediatric Patients Age 5-10 Years in Elective Surgery at Dr. Soetomo Hospital Surabaya - Herdiani Sulistyo Putri; Elizeus Hanindito; Herdy Sulistyono (Faculty of Medicine-Universitas Airlangga, 2020)
Introduction: The use of ketamine and tramadol as postoperative analgesics for pediatric are still relatively rare, especially orally administrated. As an analgesic, ketamine blocks the NMDA receptor, the main excitatory transmitter in CNS; whereas tramadol blocks serotonin and norepinephrine uptake, thus preventing pain transmission on the spinal cord. Objective: The aim of this study is to compare the effectiveness of oral ketamine and oral tramadol as analgesics for postoperative acute pain in children. Method: A double-blind randomized clinical trial was conducted at Dr. Soetomo Hospital. The hospital ethical committee had approved this study. The subject includes thirty children aged 5-10 years old who fulfilled the inclusion criteria. They were divided into either ketamine groups or the tramadol group, in which each group consisting of fifteen patients. The regimen dosage that been given was 2mg/kg tramadol and ketamine as postoperative oral analgesics in the form of simple syrup. The FLACC table was used to evaluate pain score before and after administration of drugs (30-minutes, 1-hour, 2-hours, 3-hours, 4-hours, and at discharge from the recovery room). Result and Discussion: Based on the quantitative parameter of the FLACC (scale 0-10), there was a significant difference (p<0.05) between the first-hour postoperative administration and patient discharge from the recovery room. The patient of ketamine group had far lower FLACC value compared to the tramadol group. Rescue analgesics in the form of intravenous fentanyl were given to one patient (6.7%) in the ketamine group and four patients (26.7%) in the tramadol group. Conclusion: Ketamine proved to be a better and more effective postoperative oral analgesic compared to tramadol in this study.